2018
DOI: 10.3389/fphar.2018.01296
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in mTOR and Calcineurin Signaling Pathways Are Associated With Long-Term Clinical Outcomes in Kidney Transplant Recipients

Abstract: Monitoring of immunosuppressive drugs, such as calcineurin and mTOR inhibitors, is essential to avoid undesirable kidney transplant outcomes. Polymorphisms in pharmacokinetics-related genes have been associated with variability in blood levels of immunosuppressive drugs and adverse effects, but influence of pharmacodynamics-related genes remains to be elucidated. The influence of polymorphisms in genes of the mTOR and calcineurin signaling pathways on long-term clinical outcomes was investigated in Brazilian k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…The polymorphisms PPP3CA rs3730251 (c.249G>A) and MTOR rs1135172 (c.1437T>C), rs1064261 (c.2997C>T) and rs1057079 (c.4731G>A) were analyzed by qPCR using pre-designed TaqMan SNP genotyping assays (Thermo Fisher Scientific Inc., Foster City, USA). Details about DNA extraction, genotyping assays, and qPCR procedures and quality control were previously described (21).…”
Section: Analysis Of Gene Polymorphismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymorphisms PPP3CA rs3730251 (c.249G>A) and MTOR rs1135172 (c.1437T>C), rs1064261 (c.2997C>T) and rs1057079 (c.4731G>A) were analyzed by qPCR using pre-designed TaqMan SNP genotyping assays (Thermo Fisher Scientific Inc., Foster City, USA). Details about DNA extraction, genotyping assays, and qPCR procedures and quality control were previously described (21).…”
Section: Analysis Of Gene Polymorphismsmentioning
confidence: 99%
“…However, polymorphisms in pharmacodynamics-related genes have been less explored in patients taking tacrolimusbased treatment (18,19). Our group investigated variants in genes related to calcineurin and mTOR signaling pathways and observed that MTOR, FKBP1A, FKBP2 and FOXP3 are associated with long-term impaired renal function, increased risk of acute rejection, and adverse events in kidney recipients treated with tacrolimus and everolimusbased immunosuppression (20,21).…”
Section: Introductionmentioning
confidence: 99%